In Vitro Antineoplastic and Antiviral Activity and In Vivo Toxicity of Geum urbanum L. Extracts - Maya M. Zaharieva; Lyudmila L. Dimitrova; Stanislav Philipov; Ivanka Nikolova; Neli Vilhelmova; Petar Grozdanov; Nadya Nikolova; Milena Popova; Vassya Bankova; Spiro M. Konstantinov; Dimitrina Zheleva-Dimitrova; Hristo M. Najdenski (Molecules, 2021)
This study evaluated the in vitro antineoplastic and antiviral potential and in vivo toxicity of twelve extracts with different polarity obtained from the herbaceous perennial plant Geum urbanum L. (Rosaceae). In vitro cytotoxicity was determined by ISO 10993-5/2009 on bladder cancer, (T-24 and BC-3C), liver carcinoma (HEP-G2) and normal embryonic kidney (HEK-293) cell lines. The antineoplastic activity was elucidated through assays of cell clonogenicity, apoptosis induction, nuclear factor kappa B p65 (NFκB p65) activation and total glutathione levels. Neutral red uptake study was applied for antiviral activity. The most promising G. urbanum extract was analyzed by UHPLC–HRMS. The acute in vivo toxicity analysis was carried out following OEDC 423. The ethyl acetate extract of aerial parts (EtOAc-AP) exhibited the strongest antineoplastic activity on bladder cancer cell lines (IC50 = 21.33–25.28 µg/mL) by inducing apoptosis and inhibiting NFκB p65 and cell clonogenicity. EtOAc and n-butanol extracts showed moderate antiviral activity against human adenovirus type 5 and human simplex virus type I. Seventy four secondary metabolites (gallic and ellagic acid derivatives, phenolic acids, flavonoids, etc.) were identified in EtOAc-AP by UHPLC–HRMS. This extract induced no signs of acute toxicity in liver and kidney specimens of H-albino mice in doses up to 210 mg/kg. In conclusion, our study contributes substantially to the detailed pharmacological characterization of G. urbanum, thus helping the development of health-promoting phytopreparations.